Studies on Greek and Coptic Majuscule Scripts and Books - Orsini, Pasquale (Studies in Manuscript Cultures, 2019)
The volume contains a critical review of data, results and open problems concerning the principal Greek and Coptic majuscule bookhands, based on previous research of the author, revised and updated to offer an overview of the different graphic phenomena. Although the various chapters address the history of different types of scripts, their juxtaposition allows us to identify common issues of the comparative method of palaeography.